Family identification: a beneficial process for young adults who grow up in homes affected by parental intimate partner violence - Naughton, Catherine M.; O’Donnell, Aisling T.; Muldoon, Orla T. (Frontiers in Psychology, 2015)
Exposure to parental intimate partner violence (parental IPV) is a complex trauma. Research within social psychology establishes that identification with social groups impacts positively on how we appraise, respond to and recover from traumatic events. Intimate partner violence (IPV) is also a highly stigmatized social phenomenon and social isolation is a major factor for families affected by IPV, yet strong identification with the family group may act as a beneficial psychological resource to young people who grew up in homes affected by IPV. The current study, an online survey of 355 students (M age = 20, 70% female), investigated if a psychosocial process, specifically identification with the family, may influence the relationship between the predictor, exposure to parental IPV, and outcomes, global self-esteem and state anxiety. Mediation analysis suggests that identification with the family has a positive influence on the relationship between exposure to parental IPV and psychological outcomes; exposure to parental IPV results in reduced family identification, but when family identification is strong it results in both reduced anxiety and increased self-esteem for young people. The findings highlight the importance of having a strong sense of belonging to the extended family for young people who were exposed to parental IPV, thus has implications for prevention, intervention and social policy.